Introduction and behavioral validation of the climate change distress and impairment scale - Hepp, Johanna; Klein, Sina; Horsten, Luisa K.; Urbild, Jana; Lane, Sean P. (Scientific reports, 2023)
Governmental agencies and the medical and psychological professions are calling for a greater focus on the negative mental health effects of climate change (CC). As a first step, the field needs measures to distinguish affective/emotional distress due to CC from impairment that requires further scientific and diagnostic attention and that may require treatment in the future. To this end, we constructed the climate change distress and impairment scale, which distinguishes CC distress (spanning anger, anxiety, and sadness) from impairment. In four studies (N = 1699), we developed and validated English and German versions of the scale. Across samples, spanning 2021-2022, CC distress was at least moderate, while we observed general moderate to high levels of distress and low to moderate levels of impairment. In three English-speaking samples, younger individuals and women were most affected by CC distress, whereas this was not the case in a German-speaking sample, suggesting sociopolitical influencing factors. We demonstrate convergent validity with previous measures and discriminant validity for general negative affectivity and depressive and generalized anxiety disorder symptoms, which underlines that CC distress is not in itself pathological. Employing a fully incentivized social dilemma paradigm, we demonstrate that CC distress and (to a lesser degree) CC impairment predict pro-environmental behavior, underscoring them as possible drivers, and targets, of climate-change mitigation efforts.